IDENTIFIKASI KONDISI SOSIAL EKONOMI MIGRAN DAN IMPLIKASINYA TERHADAP PERILAKU KRIMINALITAS ( STUDY KASUS DI KOTA SURABAYA ) - EKO NUR WAHYUDIONO ; Prof. Dr. M. PUDJIHARDJO, SE, MS,Dr. KHUSNUL ASHAR, SE, MA,Dr. SUSILO, SE, MS
The research aimed at knowing the socioeconomic conditions of_x000D_ criminals after migrated to Surabaya City , Indonesia, and identify the_x000D_ socioeconomic factors to the emergence of criminal behavior. The_x000D_ research is expected able to enrich and increase the knowledge of _x000D_ criminal economic behavior can be useful for the academics and_x000D_ practitioner. _x000D_ The research was done in the Surabaya City, as informants are the_x000D_ migrants that become the criminal doer in custody of the East Java_x000D_ Regional Police, City Police of Surabaya, and City Police of Tanjung_x000D_ Perak Port. _x000D_ The results showed that the socio economic conditions of the doers_x000D_ after migrated to Surabaya City is constant, because of interested in the_x000D_ urban culture that more modern to the rural area, and expect able to_x000D_ change thei r appearance and hav e ur ban c har acters , whi l e the migrant ’ s_x000D_ life standard that decrease because do not have skill to get job. _x000D_ The socio economic factors of migrant that cause the criminal_x000D_ behaviors because only graduated from Senior High Schools /Aliyah that_x000D_ were not vocational education so do not have skills to get job. Beside that_x000D_ crime is not determine by the duration of living in the Surabaya, but the_x000D_ disappointment in reaching the welfare. the criminal behaviors do not_x000D_ consider the religious precepts over the elements forced to do because_x000D_ of the demand of family economy, and the diffi cultty to get a job. _x000D_ Keywords: migrant, criminality, socio economic